Respuesta :
1.
-x = 2 - 3x + 6
-x + 3x = 8
2x = 8
x = 8/2
x = 4
2.
Step 1: 2(3x − 4) = 8 + 2x + 4
Step 2: 5x − 6 = 12 + 2x ← wrong
The correct step: Step 2: 6x − 8 = 12 + 2x
3.
The next step is 2m = 8
-x = 2 - 3x + 6
-x + 3x = 8
2x = 8
x = 8/2
x = 4
2.
Step 1: 2(3x − 4) = 8 + 2x + 4
Step 2: 5x − 6 = 12 + 2x ← wrong
The correct step: Step 2: 6x − 8 = 12 + 2x
3.
The next step is 2m = 8
Answer:
1. The correct option is 2.
2. The correct option is 2.
3. The correct option is 2.
Step-by-step explanation:
Part 1.
The given equation is
[tex]-x=2-3x+6[/tex]
Add 3x on both sides.
[tex]-x+3x=2-3x+6+3x[/tex]
Combine like terms.
[tex](-x+3x)=(-3x+3x)+(2+6)[/tex]
[tex]2x=8[/tex]
Divide both sides by 2.
[tex]\frac{2x}{2}=\frac{8}{2}[/tex]
[tex]x=4[/tex]
The value of x is 4. Therefore option 2 is correct.
Part 2.
The given equation is
[tex]2(3x-4) = 8 + 2x + 4[/tex]
Step 1: [tex]2(3x-4) = 8 + 2x + 4[/tex]
Step 2: [tex]6x-8 = 12 + 2x [/tex]
Step 3: [tex]6x-2x = 12 + 8[/tex]
Step 4: [tex]4x = 20[/tex]
Step 5: [tex]x = 5[/tex]
Student make his first mistake in step 2 and the correct step is 6x-8 = 12 + 2x. Therefore the correct option is 2.
Part 3.
The given equation is
[tex]4m-2m + 4 = -1 + 13[/tex]
Step 1: [tex]4m-2m + 4 = -1 + 13[/tex]
Step 2: [tex]4m-2m + 4 = 12[/tex]
Step 3: [tex]2m + 4 = 12[/tex]
Step 4: Subtract 4 from both sides.
[tex]2m= 12-4[/tex]
[tex]2m= 8[/tex]
The next step is 2m= 8. Therefore the correct option is 2.